2017
DOI: 10.1101/gr.217521.116
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal regulation of RNA polymerase III transcription is under the control of both the feeding–fasting response and the circadian clock

Abstract: RNA polymerase III (Pol III) synthesizes short noncoding RNAs, many of which are essential for translation. Accordingly, Pol III activity is tightly regulated with cell growth and proliferation by factors such as MYC, RB1, TRP53, and MAF1. MAF1 is a repressor of Pol III transcription whose activity is controlled by phosphorylation; in particular, it is inactivated through phosphorylation by the TORC1 kinase complex, a sensor of nutrient availability. Pol III regulation is thus sensitive to environmental cues, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
22
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 78 publications
8
22
1
Order By: Relevance
“…The liver‐regeneration response to PH in rats and to a lesser extent in mice has been extensively studied . Consistent with prior studies, (i) sham‐operated mice displayed a transient decrease in liver‐to‐body ratio; (ii) PH mice reconstituted the original liver‐to‐body weight ratio by 4 weeks (http://onlinelibrary.wiley.com/doi/10.1002/hep4.1102/suppinfo); (iii) H&E staining (http://onlinelibrary.wiley.com/doi/10.1002/hep4.1102/suppinfo) revealed little cell death but did reveal periodic increases in a staining pattern that probably reflects fat droplets, as described in detail; (iv) by 4 weeks, a normal tissue morphology was evident; and (v) the ratio of mononucleated‐to‐binucleated hepatocytes changed 3‐fold (from 2:1 to 6:1) during the course of regeneration (http://onlinelibrary.wiley.com/doi/10.1002/hep4.1102/suppinfo).…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…The liver‐regeneration response to PH in rats and to a lesser extent in mice has been extensively studied . Consistent with prior studies, (i) sham‐operated mice displayed a transient decrease in liver‐to‐body ratio; (ii) PH mice reconstituted the original liver‐to‐body weight ratio by 4 weeks (http://onlinelibrary.wiley.com/doi/10.1002/hep4.1102/suppinfo); (iii) H&E staining (http://onlinelibrary.wiley.com/doi/10.1002/hep4.1102/suppinfo) revealed little cell death but did reveal periodic increases in a staining pattern that probably reflects fat droplets, as described in detail; (iv) by 4 weeks, a normal tissue morphology was evident; and (v) the ratio of mononucleated‐to‐binucleated hepatocytes changed 3‐fold (from 2:1 to 6:1) during the course of regeneration (http://onlinelibrary.wiley.com/doi/10.1002/hep4.1102/suppinfo).…”
Section: Resultssupporting
confidence: 69%
“…We initiated these studies of cell proliferation in response to PH in the context of a multifaceted program project study of three cycles of gene expression (circadian, nutrient response, and cell division) in the mouse liver. (19)(20)(21)(22) To combine the cell-division studies using PH with the circadian and nutrient-response studies, all mice were entrained with 12-hour-light fasting and 12hour-dark feeding cycles. Thus, prior to PH, 12-14week-old mice had been first entrained for 2 weeks on 12-hour ZT0-ZT12-light/12-hour ZT12-ZT24-dark cycles to fix the circadian clock, followed by a further 2week entrainment with ZT0-ZT12-light fasting/ZT12-ZT24-dark feeding cycles, to entrain both the circadian and nutrient-response cycles.…”
Section: Resultsmentioning
confidence: 99%
“…Two recent studies 340 have reported on the inverse experiment, i.e. the application of an arrhythmic feeding protocol in wild-type animals with an intact clock [67,68]. Greenwell et al [68] observed that about 70% of mRNA rhythms were lost under these conditions, further underlining the exceptional importance of feeding-fasting cycles for hepatic gene expression rhythms.…”
Section: Interplay Between Circadian Clocks and Feeding/fasting Cyclementioning
confidence: 99%
“…We thank the CycliX Consortium: Nouria Hernandez, 1 Mauro Delorenzi, 2,3,4 Bart Deplancke, 5 Béatrice Desvergne, 1 Nicolas Guex, 6 Winship Herr, 1 Felix Naef, 5 Jacques Rougemont, 7 Ueli Schibler, 8 Teemu Andersin, 8 Pascal Cousin, 1 Federica Gilardi, 1 Pascal Gos, 8…”
Section: Acknowledgementsmentioning
confidence: 99%
“…In eukaryotes, both active and repressed genes are packaged in nucleosome-containing chromatin in which histones are reversibly modified -often reflecting the underlying gene transcription status. In this chromatin context, we study how cyclical programs of gene expression -i.e., circadian, nutrition and cell division -are regulated in differentiated cells using the mouse liver as model [1,2,3,4]. We focus on gene expression as measured by RNA-transcript levels and study the relationship between gene occupancy by RNA polymerase II (Pol II) and two specific histone modifications: histone H3 lysine 4 trimethylation (H3K4me3) observed at active promoters and histone H3 lysine 36 trimethylation (H3K36me3) associated with the body of actively transcribed genes (reviewed in [5]).…”
Section: Introductionmentioning
confidence: 99%